(untitled) (Journal of Foreign Language Studies, 2023)
The resolution of anaphoric reflexives during sentence processing is influenced by a multitude of factors, encompassing both structural constraints and non-structural constraints, including such factors as syntactic structures, gender, number, working memory capacity, retrieval cues and language proficiency among others. This paper offers a review of syntactic constraints in the processing and resolution of anaphoric reflexives, with a specific focus on Chomsky’s (1981, 1986) Government and Binding theory. It also examines the arguments put forth by both proponents and critics of the theory to provide a comprehensive analysis of syntactic constraints in the processing of reflexive-antecedent dependencies.